The Effect of Fee, Tenure, Rotation, Reputation on Audit Quality with Audit Committee as Moderator - Reschiwati, Reschiwati; Kusumaningrum, Fitra; Pratiwi, Wiwik (Journal of International Conference Proceedings, 2023)
Good audit quality can improve the quality of financial statements and the trust of the  users. This study aims to analyze the effect of Audit Fee (FEE), Audit Tenure (TNR), Audit Rotation (ROT), and Public Accounting Firm Reputation (RPT) on Audit Quality (QLT) and analyze the effect of the Audit Committee (CMT) in moderating FEE, TNR, ROT, and RPT on QLT. The research sample used purposive sampling method in financial sector service companies listed on the IDX in 2017-2022 and there were 36 companies with 216 data. The data analysis method used SPSS 25 and Eviews 13. The results showed that FEE and ROT had no effect on QLT. TNR has an effect on QLT. RPT has a negative effect on QLT. CMT strengthens the effect of TNR on QLT. CMT cannot moderate the effect of RPT on QLT. The novelty of this research is that it modifies the audit committee measurement from previous research. This research has implications for financial sector service companies so that the Audit Committee in appointing Public Accounting Firm should consider the length of time Public Accounting Firm has been engaged with the same company in a row.